AKURASI DALAM JURNALISME WARGA PADA RADIO SUARA SURABAYA - Yoanita, Desi; Lesmana, Fanny (Scriptura, 2014)
Accuracy is a very significant concept for mass media, particularly the mass media that provides space for citizen journalism. Radio Suara Surabaya maintain accuracy in the delivery of information by citizen journalists by way of clarification, lowering the SS reporter alone and have gatekeepers. The pattern of information filtering which is done by gatekeepers make citizen journalists learn how to report the information to the proper journalistic standards.This research was conducted using the case study method and data collection techniques such as interviews and observations. The result of this research found that Radio Suara Surabaya do three ways to maintain the accuracy of information from citizen journalists, namely: clarify to the competent sources, assigning reporters to the field, and create a gatekeeper team to be the filter.